Customer Value and Its Impact on Purchase Decisions in Online Shopping - Vanessa , Vanessa (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2025)
Purpose – The purpose of this research is to determine the influence of customer value on online shopping purchasing decisions (case study of Cendana Polytechnic students). Methodology/approach – The method used in this research is descriptive method, this type of research is quantitative data, primary data obtained through questionnaires. Because the population is unknown, the sampling technique used is the Lemeshow formula. It can be explained that sample calculations using the Lemeshow formula approach can be used to calculate the number of samples with an unknown population size. Thus, the number of samples used was 96 respondents and the sampling technique used accidental sampling where respondents who were met accidentally would first be used as research samples. Findings – The test results show that Customer Value partially has a positive and significant effect on online purchasing decisions. Novelty/value – It is important for companies to pay attention to customer value in order to increase online shopping purchasing decisions.